Pleural Gas Analysis for Detection of Alveolopleural Fistulae - Bharat, Ankit (Ann Thorac Surg, 2015)
PURPOSE: Visual inspection (VI) of bubbles in the chest drainage unit does not differentiate a true leak of alveolopleural fistula (APF) from a false leak. We hypothesized that detection of elevated levels of carbon dioxide, increase in oxygen content, or both, in pleural gas upon the administration of supplemental oxygen would accurately identify APF. DESCRIPTION: Prospective study comparing pleural gas analysis (GA) with VI to detect APF after surgical lobectomy (n = 50). EVALUATION: APF was found in 22 (44%) patients at the time of analysis. VI revealed air bubbles in 31 (62%) patients, indicating the presence of APF, of whom 12 (38.7%) were false leaks. VI failed to identify APF in 3 (6%) patients that resulted in post–tube removal pneumothorax. By contrast, GA accurately demonstrated APF in 21 patients, with only one false negative and no false positives. GA demonstrated better sensitivity (95.5% vs 86.4%), specificity (100% vs 57.1%), positive predictive value (100% vs 61.3%), and negative predictive value (96.6% vs 84.2%) compared to VI. CONCLUSIONS: Pleural gas analysis is an effective technique to detect APF and can facilitate timely and safe chest tube removal.